2017
DOI: 10.1016/j.amepre.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Youth Acquisition and Situational Use of Cigars, Cigarillos, and Little Cigars:

Abstract: Introduction Although adolescent use of cigars, cigarillos, and little cigars (CCLCs) has been increasing, little research has been conducted to understand how adolescents acquire CCLCs and the situations in which they smoke CCLCs. Thus, this study aims to understand how adolescent smokers acquire CCLCs and the situations in which they smoke them. Methods Data were drawn from the 2011 Cuyahoga County Youth Risk Behavior Survey. Current CCLC smoking was assessed; analysis was limited to current smokers (n=1,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Like others,16 18 we found sharing to be common among cigarillo users. The conventional method yielded higher estimates of daily cigarillo consumption than the detailed method for those who always share products.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Like others,16 18 we found sharing to be common among cigarillo users. The conventional method yielded higher estimates of daily cigarillo consumption than the detailed method for those who always share products.…”
Section: Discussionsupporting
confidence: 79%
“…Although there is no gold standard, a widely used conventional measure of tobacco consumption relies on two global questions to assess smoking days and number of tobacco products smoked on smoking days 10 11. A growing body of evidence suggests that measurement of cigarillo use may be complicated by several issues, such as variations in product terminology,12 13 manipulation of cigarillos to include marijuana14 15 and sharing of cigarillos in a group setting 16–18. While recent research has addressed some of these issues, such as using brand-specific examples and assessing subtypes of cigar products,13 19 20 to date, none have incorporated cigarillo use patterns into a measurement strategy.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with the findings from Ohio showing that 64% of underage adolescent cigar users have purchased cigars. 55 Moreover, our participants reported that bypassing underage restrictions was easier for cigars than it was for cigarettes, suggesting that stronger enforcement of underage tobacco laws is needed.…”
Section: Discussionmentioning
confidence: 89%
“…Another study found high popularity of social cigar smoking among African American youth. 20 The tendency for cigars to be smoked socially might partially explain why cigarettes and cigars were smoked additively during dual use periods.…”
Section: Discussionmentioning
confidence: 99%
“…A study with youth found that, compared with Whites, African Americans were less likely to smoke cigars in a social situation and more likely to smoke alone. 20 …”
Section: Introductionmentioning
confidence: 99%